Association between malocclusion, tongue position and speech distortion in mixed-dentition schoolchildren: an epidemiological study (Journal of Applied Oral Science, 2021)
Malocclusions are highly prevalent in childhood and adolescence, being considered a public health problem worldwide, in addition to be considered an important predictor in the tongue position and speech disorders. Objective: Evaluate the association of malocclusions with tongue position and speech distortion in mixed-dentition schoolchildren from the south of Brazil. Methodology: This cross-sectional study was performed using a database of an epidemiological survey realized in the southern of Brazil, in 2015, for evaluating the dental and myofunctional condition of the mixed-dentition from 7-13 years’ schoolchildren. The outcome variables were tongue position and speech distortion, evaluated by a trained and calibrated examiner. Characteristics regarding sociodemographic and oral health measures (Angle’s classification of the malocclusion, overjet, overbite, posterior crossbite and respiratory mode) were also assessed. Poisson regression models with adjusted robust variance were used to evaluate the association among predictors variables in the outcomes. Results are presented as prevalence ratio (PR) and 95% confidence interval (95% CI). Results: A total of 547 children were evaluated. Schoolchildren who presented anterior open bite (PR 2.36 95%CI 1.59-3.49) and having oral/oral-nasal breathing (RP 2.51 95%CI 1.70-3.71) are more likely to have altered position of the tongue. Both deep bite and being male represent protection factors for the abnormal tongue position. Regarding speech distortion, deep overbite presents a protective relationship to speech distortion (PR 0.41; 95%CI 0.24-0.71), whereas schoolchildren with posterior crossbite were more likely to present this problem (PR 1.77; 95%CI 1.09-2.88). Conclusion: Anterior open bite and posterior crossbite were the malocclusions related to speech distortion and/or altered tongue position. Oral/oral-nasal breathing was also related to myofunctional changes. Deep bite malocclusion was a protective factor for both speech problems and altered tongue position when compared to a normal overbite.